Peer-to-peer Lending Platforms «p2p» As A Financial Technology Tool In Supporting Small And Medium Enterprises - Chabani, Amina Yousra; Hammami, Raid Imade Eddine; Barkat, Mourad (جامعة الوادي - University of Eloued, 2023)
This study aims at the role of the financial technology industry in supporting emerging small and medium enterprises by highlighting the technology of peer-to-peer “P P” lending because of its potential in attracting customers, which is a form of crowdfunding and the most common one, which has led to create additional investment opportunities and expand the lending market compared to traditional banking, where we used the descriptive and analytical approach. Through this research, we investigated the role of “P P” lending platforms in bridging the financing gap that emerged after the 2008 crisis through the experience of the United States of America and their contribution to enhancing and supporting digital financing
مقال
Keywords: fintech ; peer-to-peer lending ; emerging institutions ; crowdfunding